A bibliometric analysis of financial management from Web of Science (WoS) database - Wan Mustapa, Wan Nurulasiah; Abdull Rahman, Nurul Labanihuda; Rozali, Ahmad Zulhusny; Fahri Hanafi, Hafizul; Abdull Rahman, Rabeatul Husna; Safiyuddin, Fatin Syazwani (Frontiers in Blockchain, 2025)
PurposeThis study aims to present a comprehensive knowledge mapping and an in-depth analysis of financial management research to understand better global trends and direction in this filed that emerged between 2017 and 2025.Design/methodology/approachThis study presents a visual analysis of 759 research articles listed in the Web of Science (WoS) databases between the years of 2017 and 2025 use financial management as keyword. The knowledge mapping based on VOSviewer presents the current research status, which contains the analysis of the collaboration network, co-citation network, references with citation bursts and keyword analysis.FindingsThe result that China and United States are the most prominent countries in exploring the financial management. University of California System is the most prominent instituition. Higgin Stephen, Zapounidis Constantin, Vochozka Marek and Marouskova Anne are the most prolific authors in this field.Originality/ValueThis study among the pioneers to shed lights on the current research status of financial management using the bibliometric method and the newest data. This study also suggests that collaborations between scholars and institutions require to be enhanced for better management of financial management and to contribute to sustainable development.